174k views
2 votes
3(-4x -3) + 5x -5 = 0
Solve for x

User Artych
by
4.9k points

2 Answers

1 vote

Answer:


x = - 2

Explanation:

1) Expand.


- 12x - 9 + 5x - 5 = 0

2) Simplify 12x - 9 + 5x - 5 to -7x -14.


- 7x - 14 = 0

3) Add 14 to both sides.


- 7x = 14

4) Divide both sides by -7.


x = - (14)/(7)

5) Simplify 14/7 to 2.


x = - 2

Therefor, the answer is x = -2.

User Fabiano Tarlao
by
5.5k points
4 votes

Answer:

-2

Explanation:

3(-4x-3) + 5x -5 = 0

-12x -9 + 5x -5 = 0

-7x -14 = 0

-7x = 14

-7x/-7 = 14/-7

x= -2

User Rene Duchamp
by
4.6k points